Lahirnya Identitas Baru: Pergeseran Budaya melalui Interaksi pada Karyawan Difabel Samakta Guest House - El Chris Natalia (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2019)
Cultural change and the emergence of identity in the individual can occur through interaction. Culture in an organization can form a new identity in individuals. The aim of this research is to know about the cultural shift experienced by the diffable employees who are deaf at Samakta Guest House in forming a new identity within them. The literature review used in this research includes intercultural communication, organizational culture, self-concept, and identity. This research is using a qualitative descriptive analysis. In collecting data, the researcher used an in-depth interview with four informants, ND, DD, JF, and PL. The result shows that deaf employees who work at Samakta Guest House have a special culture and identity or characteristic in themselves. Organizational culture and the process of interaction make the deaf employees become more developed and find new figures in themselves. Diffable employees adapt to new cultures. In forming this new identity, the interaction process that plays an important role in them is the interaction with the owners of Samakta Guest House and other diffable employees who work there. The substance of this research recommends that the organization, especially for the owner and manager of Samakta Guest House should develop a diffable-concerned organization.